2011
DOI: 10.1037/a0022300
|View full text |Cite
|
Sign up to set email alerts
|

The role of aesthetic sensitivity in body dysmorphic disorder.

Abstract: Individuals with body dysmorphic disorder (BDD) are excessively preoccupied with an imagined or slight defect in appearance. Higher aesthetic sensitivity in facial proportions may explain why BDD patients are severely disturbed by a small defect in their appearance.Aesthetic sensitivity can be defined as an awareness and appreciation of beauty and harmony, with three components: i) perceptual (ability to differentiate variations in aesthetic proportions); ii) emotional (degree of emotion experienced when viewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 205 publications
(424 reference statements)
1
37
3
Order By: Relevance
“…Veale, Ennis, and Lambrou (2002) found that compared to individuals with other psychiatric diagnoses, those with BDD were five times more likely to have aesthetic interests and skills, evidenced by an education or occupation in art and design. In a quasi-experimental study in which symmetry of images was manipulated, Lambrou, Veale, and Wilson (2011) found further evidence of enhanced aestheticality in BDD, in the form of perceptual acuity for symmetry in face and non-face stimuli, similar to a comparison group of individuals with an arts and design background. These authors allude to the possibility that heightened aestheticality may extend to the more general OC need for symmetry, and also, importantly, that incompleteness may be the bridge between them (Veale & Lambrou, 2002, p. 430).…”
Section: Introductionmentioning
confidence: 80%
“…Veale, Ennis, and Lambrou (2002) found that compared to individuals with other psychiatric diagnoses, those with BDD were five times more likely to have aesthetic interests and skills, evidenced by an education or occupation in art and design. In a quasi-experimental study in which symmetry of images was manipulated, Lambrou, Veale, and Wilson (2011) found further evidence of enhanced aestheticality in BDD, in the form of perceptual acuity for symmetry in face and non-face stimuli, similar to a comparison group of individuals with an arts and design background. These authors allude to the possibility that heightened aestheticality may extend to the more general OC need for symmetry, and also, importantly, that incompleteness may be the bridge between them (Veale & Lambrou, 2002, p. 430).…”
Section: Introductionmentioning
confidence: 80%
“…26 No assessment of aesthetic sensitivity has yet been conducted in patients undergoing thyroid surgery. Anecdotally, the authors have encountered patients with high aesthetic standards perceiving their scars negatively, even disproportionately so, particularly in the context of robotic-assisted thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This case was characterized by the extreme ordinariness of her background and lack of any psychiatric disorder or significant psychopathology. This may, therefore, be an example of some individuals being more aesthetically sensitive (Lambrou, Veale, & Willson, 2011;Veale et al, 1996) and just having an aversion to the appearance of normal genitalia. It may be better to accept our lack of understanding for such procedures than suggest an unknown learning history or an unconscious motivation for her desire.…”
Section: Discussionmentioning
confidence: 99%